2009
DOI: 10.1590/s1516-84842009005000073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de adultos infectados por Leishmania leishmania chagasi entre doadores de sangue do Hemocentro Regional de Montes Claros, Minas Gerais, Brasil

Abstract: O objetivo deste trabalho foi estudar a prevalência de adultos infectados por L. L. chagasi entre doadores de sangue do Hemocentro Regional de Montes Claros/MG .Realizou-se estudo epidemiológico, transversal e quantitativo, no período de 16/09/08 a 13/11/08. Participaram da pesquisa 421 doadores aptos na triagem clínica, sendo realizada imunofluorescência indireta para L.L.chagasi. Aqueles que apresentaram resultados positivos foram submetidos ao teste rápido antígeno-específico para Leishmania donovani. A aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…The high prevalence of seropositivity to L. infantum in blood donors from the endemic regions in this study confirms data reported in the Brazilian literature (Luz et al, ; Urias et al, ; França et al, ; Fukutani et al, ). This prevalence is much higher than the sum of donors considered unfit for donation due to the seven blood‐transmissible diseases compulsorily tested in the country, which in 2013 was 3·64% (ANVISA – Agência Nacional de Vigilância Sanitária, Brazil, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high prevalence of seropositivity to L. infantum in blood donors from the endemic regions in this study confirms data reported in the Brazilian literature (Luz et al, ; Urias et al, ; França et al, ; Fukutani et al, ). This prevalence is much higher than the sum of donors considered unfit for donation due to the seven blood‐transmissible diseases compulsorily tested in the country, which in 2013 was 3·64% (ANVISA – Agência Nacional de Vigilância Sanitária, Brazil, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In the northeast of Brazil, prevalence rates of 9 and 13·2% were reported in blood donors (Luz et al, ; Monteiro et al, ) and 37% in multi‐transfused patients on haemodialysis (Luz et al, ). In Minas Gerais in south‐eastern Brazil, the prevalence among donors was 5·5% (Urias et al, ) and 15·6% in the central‐west region (França et al, ), confirming the high prevalence of asymptomatic infected donors in different regions of the country. This situation, together with the proven survival of the parasite in stored blood components (Grogl et al, ), leaves recipients at risk of Leishmania infantum infection, particularly because in Brazil, like other endemic countries, transfused blood is not subject to procedures to reduce the risk of transmission.…”
mentioning
confidence: 86%
“…This finding is similar to that reported in Montes Claros (5.5%) {[33] #265} but lower than that observed in Natal (9%) {[20] #10} and in Campo Grande (15.6%) {[21] #262}, both of which are endemic regions for VL. The lower prevalence detected in our study may be due to the fact that Salvador is not a VL endemic area per se , differently from the other three municipalities.…”
Section: Discussionsupporting
confidence: 87%
“…The lower prevalence detected in our study may be due to the fact that Salvador is not a VL endemic area per se , differently from the other three municipalities. Additionally, differences in the sensitivity of the tests employed herein (SLA-based ELISA) versus those used in Natal (FML-ELISA) {[20] #10}, Montes Claros and Campo Grande (IFAT) {[33] #265; [21] #262} may contribute for the differing results. In our study, an ELISA assay employing L. amazonensis SLA was less sensitive when compared to L. infantum SLA (Figure 1), suggesting that the choice of antigen impacts on the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In endemic areas, however, serology (rapid test and indirect fluorescent antibody test) is positive for a considerable percentage of asymptomatic individuals. 47 This feature precludes ruling out the possibility that patients diagnosed exclusively by positive serology died from another undetected underlying disease, despite the efforts made, during hospitalisation, to achieve differential diagnosis and rule out other conditions. Concomitant use of two or more antileishmanial drugs did not influence mortality rate.…”
Section: Discussionmentioning
confidence: 99%